Comparison between standard and drift reducing nozzles for pesticide application in citrus: Part I. Effects on wind tunnel and field spray drift - Torrent, Xavier; Garcerá, Cruz; Moltó, Enrique; Chueca, Patricia; Abad-Moyano, Raquel; Grafulla, Carmen; Román, Carla; Planas, Santiago (2018)
The objective of this study was to evaluate and to compare spray drift potential and field spray drift from pesticide application in citrus orchards carried out mainly comparing standard nozzles with drift reducing nozzles. Two different standard nozzles (hollow cone and full cone) and one Venturi drift reducing nozzle (hollow cone) were tested. Spray drift potential was measured by means of wind tunnel experiments (ISO 22856:2008 method). To estimate field airborne and sedimenting spray drift, two trials with 5 replicates each were carried out (ISO 22866:2005 method) in two different commercial orchards of Clementine mandarins. Results showed that Venturi nozzles significantly reduced drift with the two methodologies. Moreover, the wind tunnel method showed the same trend as the field results. Additionally, spray drift deposition variability was lower for the Venturi nozzles. Therefore, it could be concluded that Venturi nozzles can be recommended to be used in citrus orchards to prevent human and environmental risks and their use could be appropriate for different scenarios where spray drift risk must be mitigated. (C) 2017 Elsevier Ltd. All rights reserved.